The pest kill rate of thirteen natural enemies as aggregate evaluation criterion of their biological control potential of Tuta absoluta - Lenteren, Joop C. van (2021)
Fil: Lenteren, Joop C. van. Wageningen University. Laboratory of Entomology. Wageningen, The Netherlands.